Barriers and facilitators to the implementation of PHAROS, a perioperative pharmaceutical management intervention for older adults – a qualitative interview study from the perspective of healthcare providers - Moritz Sebastian Schönfeld; Julia Rinke; Claudia Langebrake; Levente Kriston; Cynthia Olotu; Rainer Kiefmann; Corinna Bergelt (BMC Geriatrics)
Abstract Background Number of drugs are increasing with older age and present a risk factor for various adverse health outcomes. A comprehensive medication therapy management (MTM) before admission for elective surgery may help reduce unnecessary and potentially inadequate medications (PIM) and thus improve patient health. Our goal was to evaluate the implementation of PHAROS, a perioperative MTM intervention study, from the perspective of health care providers. The PHAROS intervention aimed to improve medication appropriateness in older inpatients at the outpatient / inpatient interface. Methods We performed a qualitative interview study within a pilot intervention study comparing a comprehensive MTM with standard care in older inpatients (≥ 65 years) in Germany. Semi-structured interviews with health care professionals were performed from March to July 2021. The Consolidated Framework for Implementation Research (CFIR) was used to guide development of interview guide, data coding, analysis, and reporting of findings. Results Ten health care professionals involved in the implementation of PHAROS were interviewed. Based on CFIR-constructs, facilitators included need for and meaningfulness of the intervention as well as positive and supportive cooperation within the project team. Implementation of MTM at the interface of inpatient to outpatient care before elective surgery was hampered by personal and organizational barriers as well as barriers resulting from broader health care structures in Germany. In particular, lack of documentation standards, missing compatibility with clinical workflow, difficulties in stakeholder engagement, as well as communication barriers between outpatient and inpatient care interfaces hindered implementation of the intervention. Conclusions Further studies should consider focusing on facilitators to pharmaceutical implementations such as transparent and clear communication structures between stakeholders, standardization of medication documentation, and intervention structures that are adapted to hospital workflows. Trial registration https://drks.de Identifier: DRKS00014621, this study was part of the PHAROS study.